POTENSI PENGELOLAAN ZAKAT, INFAQ DAN SHADAQAH DALAM MEMBANGUN PEMBERDAYAAN EKONOMI UMMAT DAN KESEJAHTERAAN MUSTAHIQ (studi kasus LAZISMU Kota Probolinggo) - muhammad alfi syahrin; Isma Swadjaja (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2021)
LAZISMU Probolinggo City is one of the institutions that manages and distributes zakat, infaq and shadaqah, see the importance of zakat, infaq and shadaqah and their management because they have great potential in building the  ummat economic empowerment and the mustahiq welfare.  The purpose of this research is to knowing the management of zakat, infaq and shadaqah in LAZISMU Probolinggo City and the potential management of  zakat, infaq and shadaqah in building the ummat economy and mustahiq welfare in LAZISMU Probolinggo City.  This research is a field research with qualitative methods.  The methods used in data collection are observation, interview, and document study.  The data that has been collected are then compiled and analyzed using descriptive methods.  The results showed that the potential managrment of zakat, infaq and shadaqah is quite good in implementing economic the ummat empowerment  and the mustahiq welfare, as evidenced by the several programs that have been implemented, some mustahiq can begin to gradually leave the deprived lives to become more independent and far away there is hope to become muzakki from the results of the business he is running.Keywords : management of zakat, infaq and shadaqah, ummah economic empowerment, mustahiq welfare